(untitled) (Research, Society and Development, 2022)
The essay establishes historical correlations between social engineering and eugenics measures, affecting access to health care for people with disabilities during the Pandemic in Brazil. Historical circumstances date back to “ideals” proposed by the Eugenics Leagues, affect equity in the health of people with disabilities during this health crisis. Ethical aspects related to the Covid-19 and disability relationship are examined in view of the justification of the scarcity of resources in the Pandemic. Exposed between “make live, let die”, we seek to understand the impacts of the pandemic on the existential territories of people with disabilities. It reflects on the “guidelines” and “clinical assessments” that historically allow themselves to be crossed by the governmentality of discursive practices, affecting the bodies of subjects and the “body of society”. The economistic logic permeates the recommendations of corporeal “medical knowledge”, normative bodies that will be prioritized, to the detriment of population segments exposed to the disease. This biodeterminism applied to the screening of Covid-19 victims, addressed in Milićević’s work, explains the use of disability as a factor in denial of treatment. The “normal”/“abnormal” antinomy is reinstated in an attempt to neutralize necropolitics in the face of Covid-19. The essay refers to Foucault deploying the biopolitics of the medical apparatus to deal with the population as a scientific and political problem. In order to consider the biodeterminism that suppresses the rights of subjects, we turn to Engelhardt’s postmodern bioethics, examining the emergency care of people with disabilities. The manuscript follows a bioethical path that debates equity in health and efficiency in the allocation of resources. Finally, it reflects on ways in which society can contribute in the post-pandemic world, ethically and aesthetically privileging existential territories of people with disabilities.